In and out of Brussels : figuring postcolonial Africa and Europe in the films of Herman Asselberghs, Sven Augustijnen, Renzo Martens, and Els Opsomer - Demos, T. J.; Van Gelder, Hilde (Leuven : Leuven university press, 2012)
This book examines four Brussels-based artistic projects that converge in critically investigating the figuration of Africa in the image economy of the West: Herman Asselberghs's 'Speech Act' (2011), Sven Augustijnen's 'Spectres' (2011), Renzo Martens's 'Episode III - Enjoy Poverty' (2008) and Els Opsomer's 'Building Stories: That Distant Piece of Mine' (2012). While each is a singular film, together they reveal Africa's postcolonial imaginary to be a zone of crisis, situated between humanitarian emergency, financial pillage, and the politics of memory on the one hand, and the fictional - but nonetheless consequential - construction of European identity on the other. Just as dominant neocolonial narratives (which all too often cover over movements for independence and social justice) are critically played out and contested in these works, so too are documentary conventions creatively reinvented by Asselberghs, Augustijnen, Martens, and Opsomer.
boek